Evaluasi Supply Chain Pada Pabrik Beras Jaya Subur Makmur di Kota Karawang - Aditya Duta Pangestu; Muhammad Nazarudin; Santi Pertiwi Hari Sandi; Dwi Epty Hidayat (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
The Jaya Subur Makmur rice factory is a food processing plant founded by Mr. Abdul Muhyi in 1986. In terms of Supply Chain Management (SCM) studies, one of the root problems in the post-harvest rice commodity business is distribution problems. The low accessibility of commodity availability information for stakeholders results in the distribution process not going well, resulting in frequent accumulation of commodities and commodity vacancies on the other side. The aim of the study was to find out how to evaluate the performance of rice supply chain management at the Jaya Subur Makmur rice factory. This research is classified as a qualitative type using primary data from interviews and direct observation..